Record of a gregarine (Apicomplexa : Neogregarinida) in the abdomen of the termite Coptotermes gestroi (Isoptera, Rhinotermitidae) - Costa-Leonardo, Ana Maria [UNESP]; Casarin, Fabiana E. [UNESP]; Constantini, Joice P. [UNESP] (Academic Press Inc. Elsevier B.V., 2008)
Coptotermes gestroi is an exotic species of termite that is a pest of great economical importance in Brazil. This paper relates the occurrence of a coelomic gregarine (Apicomplexa: Neogregarinida) in the abdomen of the foraging workers recently collected from field colonies of this termite. The termite hosts presented large, white abdomens because they carried 1 up to 3 cysts of gregarines filled with numerous lemon-shaped spores. Earlier developmental stages of this gregarine were not observed in the scanning microscope preparations nor in the histological slides of the infected termites. However, the lemon-shaped spores suggest a parasite gregarine of Mattesia genus, family Lipotrophidae. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: gregarine cyst; termite; Isoptera; Rhinotermitidae; Mattesia; Neogregarinida